2023
DOI: 10.3390/biomedicines11092443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cartilage Integrity following Administration of Oral and Intraarticular Nifedipine in a Murine Model of Osteoarthritis

Viktorija Aleksiuk,
Justinas Baleisis,
Gailute Kirdaite
et al.

Abstract: Osteoarthritis (OA) ranks as the prevailing type of arthritis on a global scale, for which no effective treatments are currently available. Arterial hypertension is a common comorbidity in OA patients, and antihypertensive drugs, such as nifedipine (NIF), may affect the course of OA progression. The aim of this preclinical study was to determine the effect of nifedipine on healthy and OA cartilage, depending on its route of administration. In this study, we used the destabilization of medial meniscus to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…We did not record the medication taken by the patients, but in terms of frequency, the most frequently prescribed medications in France are angiotensin II receptor blockers and diuretics followed by beta-blockers, calcium channel blockers, and angiotensin-converting enzyme (ACE) inhibitors [30]. Several experimental studies [31][32][33][34][35][36][37][38][39][40] have shown that certain antihypertensives have potentially beneficial effects on OA, whether through anti-inflammatory, antioxidant, analgesic, or even antidegenerative effects. Our work is therefore in line with the literature on the potential chondroprotective effect of certain antihypertensive medications, but as we did not record the medications, we cannot draw any conclusions in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…We did not record the medication taken by the patients, but in terms of frequency, the most frequently prescribed medications in France are angiotensin II receptor blockers and diuretics followed by beta-blockers, calcium channel blockers, and angiotensin-converting enzyme (ACE) inhibitors [30]. Several experimental studies [31][32][33][34][35][36][37][38][39][40] have shown that certain antihypertensives have potentially beneficial effects on OA, whether through anti-inflammatory, antioxidant, analgesic, or even antidegenerative effects. Our work is therefore in line with the literature on the potential chondroprotective effect of certain antihypertensive medications, but as we did not record the medications, we cannot draw any conclusions in this respect.…”
Section: Discussionmentioning
confidence: 99%